Metabolic Changes in the Myocardium during Adrenaline-Induced Injury and the Effect of Heart Cryoextract on Lactate-Pyruvate Metabolism - Mykola O. Chyzh; Fedir Vol. Hladkykh; Tetiana I. Liadova; Mariia S. Matvieienko; Roman R. Komorovsky (Український журнал серцево-судинної хірургії, 2025)
Metabolic injury to the myocardium during excessive adrenergic stimulation is primarily mediated by overstimulation of β-adrenergic receptors, resulting in a cascade of biochemical and structural changes that lead to myocardial toxicity.